2014
DOI: 10.1152/japplphysiol.00651.2014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of middle cerebral artery diameter during hypocapnia and hypercapnia in humans using ultra-high-field MRI

Abstract: In the evaluation of cerebrovascular CO2 reactivity measurements, it is often assumed that the diameter of the large intracranial arteries insonated by transcranial Doppler remains unaffected by changes in arterial CO2 partial pressure. However, the strong cerebral vasodilatory capacity of CO2 challenges this assumption, suggesting that there should be some changes in diameter, even if very small. Data from previous studies on effects of CO2 on cerebral artery diameter [middle cerebral artery (MCA)] have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
214
20

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(274 citation statements)
references
References 26 publications
13
214
20
Order By: Relevance
“…The observation that RAP is not influenced by age either, is also noteworthy since changes in RAP have been associated with the myogenic control of small blood vessels as one of the main mechanisms responsible for an active CA (Panerai et al 2005). On the other hand our results agree with the wellknown increase in BP and HR with age and previously reported reductions in CBFV and EtCO2 in older subjects (Mancia et al 1980, Verbree et al 2014. Taken together, these results suggest that estimates of ARI, phase or RAP do not need to be corrected for age.…”
Section: Influence Of Agesupporting
confidence: 90%
“…The observation that RAP is not influenced by age either, is also noteworthy since changes in RAP have been associated with the myogenic control of small blood vessels as one of the main mechanisms responsible for an active CA (Panerai et al 2005). On the other hand our results agree with the wellknown increase in BP and HR with age and previously reported reductions in CBFV and EtCO2 in older subjects (Mancia et al 1980, Verbree et al 2014. Taken together, these results suggest that estimates of ARI, phase or RAP do not need to be corrected for age.…”
Section: Influence Of Agesupporting
confidence: 90%
“…Middle cerebral artery mean velocity and CBF have in the past been shown to being highly correlated. 38 However, recent studies have reported changes in vessel diameter in response to hypercapnia and hypoxia 3,18,19 albeit of greater magnitude, than those induced in the present study. In the present study, PetCO 2 was elevated 10 mm Hg above resting values, whereas changes in MCA diameter have been reported only with increases in 15 mm Hg or more.…”
Section: Discussioncontrasting
confidence: 70%
“…It is now clear that the diameter of the MCA (and hence possibly the PCA) is influenced by marked changes in arterial PCO 2 (>8 mmHg above or below resting) and arterial PO 2 (<50 mmHg) 84,96 (reviewed in literature 9,97 ). It is less clear that changes in blood pressure will affect the diameter of these intra-cranial arteries.…”
Section: Transcranial Dopplermentioning
confidence: 99%